Yam breeding at IITA: achievements, challenges, and prospects - López Montes, Antonio José; Bhattacharjee, Ranjana; Girma Tessema, G. (2012)
African food system Yam (Dioscorea spp.) is a multispecies, clonally propagated crop cultivated for its starchy tubers. About 10 species are widely cultivated around the world, but only D. rotundata, D. alata, and D. cayenensis are the most widely cultivated species in West Africa, accounting for 93% of the global yam production. Since inception, IITA R4D efforts have focused on developing new varieties of yam with desired agronomic and quality traits and to improve yam-based cropping systems.